PENGARUH KEPEMILIKAN MANAJERIAL, GROWTH OPPORTUNITY, DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2016-2018) - Endang Fitriani; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to determined the effect of managerial ownership, growth opportunity, and leverage on accounting conservatism during the 2016-2018 period. The variables examined in this study are managerial ownership, growth opportunity, and leverage as independent variables, accounting conservatism as the dependent variable. The research method used is descriptive statistical method. By testing verification using multiple linear regression with IBM SPSS Statistic program version 22. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during the period 2016-2018. The data used is secondary data, namely the annual report of the company that was sampled in the study. The research sample was 28 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018 which were taken using the Purposive Sampling method. The results of this study indicate that managerial ownership and growth opportunity have no significant effect on accounting conservatism, but leverage has a significant negative effect on accounting conservatism.Keywords : Managerial Ownership, Growth Opportunity, Leverage, Accounting Conservatism